Tax Digitalization, Tax Incentives and Smes Taxpayer Compliance: The Moderating Role of Public Trust - Alifvia, Febby Perlica Nur; Kresnawati, Etik (Universitas Muhammadiyah Yogyakarta, 2023)
In 2022 the government is trying to continue to increase the tax ratio. One of which is by maximizing taxpayer compliance, including for Small and Medium Enterprises (SMEs) sector. Fiscal review in 2022 estimated that SMEs in Special Region of Yogyakarta growth has reached an average of 8.45 percent per year with turnover growth reaching 1.37 percent per year. However, the growth in the number of SMEs is not accompanied by greater tax revenues as indicated by the low tax revenues of SMEs. This study examines the effect of tax digitalization and tax incentives on SMEs taxpayer compliance, moderated by public trust. The research data was collected by distributing questionnaires online and offline. Based on 75 respondents which were determined by the purposive sampling method, the results of the SEM-PLS analysis show that tax digitalization and tax incentives have positive effect on SMEs taxpayer compliance as hypothesized. Meanwhile, instead of moderating the two independent variables on SME taxpayer compliance, public trust becomes an important variable that that can improve SME taxpayer compliance. The finding would suggest that local governments can increase the participation of SMEs as a support for local revenue by encouraging tax compliance through tax digitalization and tax incentives as well as public trust.